Decentralization and Collusion - Sandeep Baliga; Tomas Sjostrom (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
We consider a model where agents work in sequence on a project, share information not available to the principal, and can collude. Due to limited liability the Coase theormem does not apply. The distribution of surplus among the agents is there an important control variable for the principal, which gives us a theory of how to delegate in an organization subject to moral hazard. The optimal distribution of surplus can always be achieved by delegating in the right way (decentralization) without using "message games" (centralization).
Keywords: 330